Clinical significance of family accommodation and parental psychological distress in a sample of children and adolescents with obsessive-compulsive disorder aged 8-17 years old - Maria Pontillo; Francesco Demaria; Maria Cristina Tata; Roberto Averna; Prisca Gargiullo; Maria Laura Pucciarini; Ornella Santonastaso; Tommaso Boldrini; Alberto Eugenio Tozzi; Stefano Vicari (BMC, 2020)
Abstract Background Family Accommodation (FA) refers to the involvement of family members (especially parents) in the compulsive behaviors of children and adolescents with Obsessive-Compulsive Disorder (e.g. modifying family routines or facilitating avoidance of obsessive-compulsive triggers). Many studies have examined the high prevalence of FA in this clinical population; however, less is known about its clinical significance and relationship to the individual psychological distress of parents. In our study, we investigated the clinical significance of FA examining its relationship with obsessive-compulsive symptomatology, functioning, anxiety and depressive symptoms in a clinical sample (n = 51) of children and adolescents with Obsessive-Compulsive Disorder (OCD) aged 8-17 years old and their parents, included to examine their individual psychological distress. Methods The sample was divided into two groups: the High Accommodation group (n = 36) and the Low Accommodation group (n = 15). Results Results demonstrated that children and adolescents in the OCD High Accommodation group reported major functional impairment in global (p = .001313), social (p = .000334) and role (p = .000334) domains, and higher depressive symptoms than the Low Accommodation group. Both fathers and mothers from the High Accommodation group reported a higher level of individual psychological distress compared to mothers and fathers from the Low Accommodation group (p = .040365). Conclusions The findings of this study show that FA is common in children and adolescents with OCD and it could cause not only an impairment of the patient's global, social and role functioning but also a high level of individual psychological distress in the single parent. The presence of FA should therefore be carefully investigated and considered in planning assessment and treatment of OCD in children and adolescents.